PENGARUH KARAKTERISTIK PERUSAHAAN DAN BEBAN IKLAN TERHADAP TINDAKAN PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR - Octivia Rian Fatmawati; Akhmad Solikin (Politeknik Keuangan Negara STAN, 2017)
This study aims at analyzing the influence of company characteristics and advertising expenses on the tax avoidance. Object of the study are manufacturing companies listed on the Indonesia Stock Exchange in the period of 2010-2014. Determination of the sample is done by using purposive sampling method by taking into account some characteristics of the companies and their annual reports. By applying panel data regression, it turns out that advertising expense is significant predictor of tax avoidance which is proxied by effective tax rate. Regarding companies’ characteristics, liquidity, size, and profit quality influence tax avoidance. Tax administration could use the results from this study to further identify manufacturing companies prone to tax avoidance.